Intravenous solution therapy simplified - G.W. Schepers (AOSIS, 1982)
The Health Matters Advisory Committee, a statutory body constituted under the Health Act 63 of 1977, appointed a National Intravenous Infusion Rationalisation Committee, consisting of experts from the medical and pharmaceutical professions to investigate and make re commendations regarding the availability and use of intravenous solutions in South Africa with the view to promoting patient safety, simplifying therapy for the clinicians, and providing economy for both the producer and the consumer. When the recommendations are implemented the range of formulations will be reduced from 103 to 41 and containers from over 70 to 21. Considerable modification will result in improvements and ultimate standardisation of administration sets and packs.